IMPLEMENTASI PEMBELAJARAN KOOPERATIF DALAM MEMBANTU MENGEMBANGKAN KECERDASAN EMOSIONAL - Sujarwo, Sujarwo (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Application of learning models are not only directed to the achievement of learning outcomes that are cognitive, but also how to able to enhance students 'skills in working together, to interact socially, and to develop students' emotional intelligence and multiple intelligence or social skills. The development of emotional intellegence can affect the process and the success of subsequent learning, because learning is not merely a question of intellectual, but also development of students' emotional intelligence. Learning is not just interaction with learning resources, books, and environments, but also involves humanic relationships among students, between students and teachers, and students with their environment. The elements of emotional intelligence include: self-awareness, self-regulation, motivation, empathy and social skills. Emotional intelligence in this analysis is limited to the activity of students in the learning process, ie: student self-control skills to motivate themself, to have a high spirit and to be adious in learning, and skills to interact with fellow students and teachers in the learning process. Student interaction can occur during the learning process that is on cooperative learning, interaction in group discussions both individually and in groups.